An intensional perspective on the semantic and pragmatic web. (15th September 2011) - Aaberge, Terje; Akerkar, Rajendra; Boley, Harold
In recent years, there has been increasing interest in the pragmatic web as an extension of the semantic web. After preliminary sketches and initial ideas, more formal attempts at characterising and defining pragmatic aspects of the web have recently emerged. Although some amount of scientific research and a number of applications have appeared under the name of the pragmatic web, there is not yet a common agreement on what the pragmatic web should be and how it should be formalised. In this paper, we consider the pragmatic web to be an augmentation of the semantic web with virtual agents exploiting web content on behalf of human contractors.